Bio-Based Modification of Natural Rubber-Modified Asphalt Using Hard Resin from Yang - Sinthorn, Poramin; Tirapat, Supakorn; Katekaew, Somporn; Wongsa, Ampol; Posi, Patcharapol; Thongchom, Chanachai; Chindaprasirt, Prinya (Salehan Institute of Higher Education, 2025)
This study investigates the potential of hard resin derived from the Yang tree (HY), a renewable bio-based byproduct, as a performance-enhancing additive in natural rubber-modified asphalt (NRMA). HY-modified binders (HYMA) containing 3%, 7%, and 15% HY by weight were evaluated through a multi-scale experimental program, including physical, rheological, thermal, chemical, and mechanical tests. Standard binder characterizations (penetration, ductility, softening point, viscosity), spectroscopic analyses (FT-IR, NMR), microstructural observations (ESEM, XRD), thermal profiling (DSC), and performance assessments (DSR, Marshall) were conducted. The results demonstrated that HY improved binder properties at optimal concentration by introducing additional hydrocarbon structures without chemical cross-linking. HYMA3 achieved the most favorable balance of stiffness, flexibility, and compaction efficiency, whereas higher HY contents (≥7%) impaired structural integrity and deformation resistance. Microstructural and thermal evidence confirmed surface modifications and altered thermal transitions, which influenced viscoelastic response. These findings provide new insights into bio-resin–asphalt interactions and establish the viability of HY as a sustainable alternative to synthetic polymer modifiers. Beyond performance improvement, HY promotes circular construction by transforming agricultural byproducts into functional pavement materials, supporting the development of climate-adaptive infrastructure.